Interaction between trace element (Sulphor - copper- Molebdenum) in human\'s body - G Vaghari (Tehran University of Medical Sciences, 2000)
Interaction between trace element such as Copper, Molybdenum and Sulphor affecting not only on the rate of Absorption, but also on the metabolic activity. The studies has shown that excessive expense of full diet sulphor decreases notonly molybdenum's absorption, but also demineralization of tissue from above elements . Also interaction between molybdenum and copper decreases body availability to these elements. Review of the literature indicates that in longtime exessive expense of full diet solphor and osteoproses copper in tissue, that it,s more current clinical sign is anemia and osteoprosis . Also this idia can prove . full sulphor combination can be used for treating. The palientseffected by high cappes in body should be treated like wilson's disease .